Serum copper levels and risk of major adverse cardiovascular events: a systematic review and meta-analysis - Muñoz-Bravo, Carlos; Soler-Iborte, Eva; Lozano-Lorca, Macarena; Kouiti, Malak; González-Palacios Torres, Carla; Barrios-Rodríguez, Rocío; Jiménez-Moleón, José Juan (Frontiers in Cardiovascular Medicine, 2023)
Background: Despite the fact that several studies have investigated the association between serum copper levels (S-Cu) and the risk of cardiovascular diseases, this relationship remains unclear. The aims of this study were to investigate the association between S-Cu and risk of major adverse cardiovascular events (MACE), including total stroke, ischemic stroke, hemorrhagic stroke, myocardial infarction and cardiovascular mortality, and identify potential sources of results heterogeneity Methods: We carried out a systematic review and meta-analysis. The selection criteria were: 1) Observational studies (cohort studies, case-control studies and hybrid studies); 2) Studies containing quantitative data about the relationship between S-Cu and risk of MACE; 3) Estimating association measures; and 4) Studies written in English, French or Spanish. Overall pooled Odds ratio (pOR) and 95% confidence intervals (95% CI) of MACE for the highest vs. lowest S-Cu category were calculated using random-effects models. Results: SixteenFifteen studies with a total of 410,32662 participants were included in the meta-analysis: 109 prospective cohort studies, 5 nested case-control studies and 1 case-control study. Comparing highest vs lowest category, high S-Cu levels were associated with total stroke (pOR: 1.49, 95% CI 1.22 – 1.82; I2 = 0%, p = 0.54), myocardial infarction (pOR: 1.6031, 95% CI 1.3917 – 1.846; I2 = 0.0%, p = 0.92) and cardiovascular mortality (pOR: 1.68, 95% CI 1.42 – 1.99; I2 = 0.0%, p = 0.547). Subgroup analysis showed that studies with a hybrid design had higher risks for cardiovascular mortality (pOR: 3.42, 95% CI 1.98 – 5.92) and ischemic stroke (pOR: 1.54, 95% CI 1.30 – 1.83). Conclusion: High S-Cu levels were associated with an increased risk of total stroke, myocardial infarction and cardiovascular mortality. Hybrid studies seems to modify the strength of the association between S-Cu and the risk of cardiovascular mortality and ischemic stroke. Systematic review registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022370782, identifier: CRD42022370782